Nebulized Hyaluronan Ameliorates lung inflammation in cystic fibrosis mice12. Issue 8 (23rd July 2012) - Gavina, Manuela; Luciani, Alessandro; Villella, Valeria R.; Esposito, Speranza; Ferrari, Eleonora; Bressani, Ilaria; Casale, Alida; Bruscia, Emanuela M.; Maiuri, Luigi; Raia, Valeria
Abstract Rationale Chronic lung inflammation with increased susceptibility to bacterial infections cause much of the morbidity and mortality in patients with cystic fibrosis (CF), the most common severe, autosomal recessively inherited disease in the Caucasian population. Exogenous inhaled hyaluronan (HA) can exert a protective effect against injury and beneficial effects of HA have been shown in experimental models of chronic respiratory diseases. Our objective was to examine whether exogenous administration of nebulized HA might interfere with lung inflammation in CF. Study design/methods F508del homozygous mice (CftrF508del) and transgenic mice overexpressing the ENaC channel β‐subunit (Scnn1b‐Tg) were treated with nebulized HA (0.5 mg/mouse/day for 7 days). Tumor necrosis factor‐alpha (TNFα), macrophage inflammatory protein‐2 (MIP‐2), myeloperoxidase (MPO) levels, and macrophage infiltration were assessed on lung tissues. IB3‐1 and CFBE41o‐epithelial cell lines were cultured with HA (24 hr, 100 µg/ml) and Reactive Oxygen Species (ROS), Tissue Transglutaminase (TG2) SUMOylation and Peroxisome Proliferator Activated Receptor gamma (PPARγ) and phospho‐p42/p44 levels were measured by dichlorodihydrofluorescein assay, or fluorescence resonance energy transfer (FRET) microscopy or immunoblots. Results Nebulized HA reduced TNFα expression (P < 0.005); TNFα, MIP‐2, and MPO protein levels (P < 0.05); MPO activity (P < 0.05); and CD68+ cells counts (P < 0.005) in lung tissues of CftrF508del and Scnn1b‐Tg mice, compared with saline‐treated mice. HA reduced ROS, TG2 SUMOylation, TG2 activity, phospho‐p42‐44, and increased PPARγ protein in both IB3‐1 and CFBE41o cells (P < 0.05). Conclusions Nebulized HA is effective in controlling inflammation in vivo in mice CF airways and in vitro in human airway epithelial cells. We provide the proof of concept for the use of inhaled HA as a potential anti‐inflammatory drug in CF therapy. Pediatr Pulmonol. 2013; 48:761–771. © 2012 Wiley Periodicals, Inc.